The Education of Roman Law from 1874 to 1894 in Japan. The Transition of Contemporary Model of Legal Systems in the West and the Intellectual Backgrounds of Professors in Charge of Roman Law - Hayashi, Tomoyoshi (Acta Universitatis Lodziensis. Folia Iuridica, 2022)
This article focuses on the position of Roman law in Japanese legal education from 1874 to 1894. Japanese law was drastically Westernised during this period, taking inspiration from Europe, and was modelled after common law and French law simultaneously. German law then became more dominant at the end of the period. All professors from Europe, regardless of their country of origin or legal background, unequivocally emphasised the importance of Roman law as the common basis of Western laws when teaching their Japanese pupils. Some of those pupils later contributed substantially to academic arguments on Roman law. Most notably, this period secured the place of Roman law in modern legal education in Japan.